Designing with models : a studio guide to architectural process models - Mills, Criss (Hoboken, N.J. : Wiley, 2011)
This text focuses on the design model as an agent in the design process and outlines a variety of materials, tools and techniques used to construct models. It contains photographs illustrating the techniques used to create architectural models.
Designing with Models, Third Edition is the revised, step-by-step guide to basic and advanced design process modeling. This comprehensive text explains the process from start to finish, and has been expanded to include up-to-date information on digital modeling programs and rapid prototyping processes.
Acknowledgments. Foreword. Introduction. Model History. Chapter 1. Model Types: Typical Model Types Employed in the Design Process. Chapter 2. Exploration: A Framework for Conceiving and Using Models in the Design Process. Chapter 3. Project Development: Academic Examples in Support of Exploration. Chapter 4. Project Development in Practice: Design Firm Examples in Support of Exploration. Chapter 5. Rapid Prototyping: Rapid Prototyping Using Digital Information to Produce Physical Models. Chapter 6. Digital Practice: Combining Digital and Physical Model Information in Professional Practice. Chapter 7. Basic Assemblage: Basic Techniques for Assembling Model Components. Chapter 8. Advanced Assemblage: Advanced Techniques for Form Making. Chapter 9. Assemblage Case Studies: Step-by-Step Case Studies of Assembly Techniques. Chapter 10. Tools: Equipment & Materials. Appendix: Topics for Continuing Exploration. Credits.
Includes index.
Includes bibliographical references and index.
Keywords: Architectural models -- Handbooks, manuals, etc